Nuclear Factor-kappa B Gene Polymorphism and Interleukin-8 in Iraqi Population with Severe Chronic Periodontitis - Raghad Fadhil (Journal of Global Pharma Technology, 2019)
Background: Periodontitis is characterized by an unbalanced host response to periodontopathogens, which lead to periodontal tissues breakdown. Genetic backgrounds play a key role in susceptibility to and protection against a spectrum of periodontal diseases. Interleukin-8 is a relevant mediator of granulocyte accumulation by attracting polymorphnuclears in the inflammatory region.  Nuclear factor kappa B (NF-kB) is a key regulator during inflammatory process involving the gingiva and alveolar bone of teeth.  Aim of study: case control study used to explore the correlation between polymorphisms in NF-kB-94 gene and serum level of IL-8 and the impact of polymorphisms on the degree of susceptibility to and severity of chronic periodontitis. Materials and methods: Ninety six Iraqi subjects their age range (30-50) years were included in study divided in to two groups (patients with chronic periodontitis and healthy control), venous blood were collected from each patients for immunological analysis of IL-8 and genetic analysis forNF-kB-94. Results: The present study revealed a significant decrease in the median serum level of IL-8 (p< 0.029) among patients group (78.9pg/μl) as compared to controls group (80.4pg/μl). For genetic analysis after sequencing with sanger method two polymorphisms were detected in the promoter region of NF-κB1-94 at rs28362491 and rs569599236 as there was deletion in the sequence of ATTG for rs28362491 while there was deletion in the sequence GCA for rs569599236 with non-significant association with chronic periodontitis group although significant association was reported with serum level of IL-8 and bleeding on probing index. Conclusion: The results suggest that the ins/del ATTG polymorphisms in NF-kB1-94 is associated with increased severity of developing periodontitis, since this study have documented that polymorphisms located within genes encoding cytokines regulated by NF-κB have association with disease activity.Keywords: Chronic periodontitis, IL-8, NF-κB, gene polymorphisms.